2013
DOI: 10.1007/s40368-013-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care in children with haemophilia in Helsinki, Finland

Abstract: Dental care during hospital visits in children with haemophilia may enhance confidence in the preventive dental care and help minimise bleeding during dental procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Sixteen studies involved individuals with hemophilia from hospitals or centers specialized in hematological treatment [4,6,7,9,12,14,[18][19][20]30,31,[33][34][35][36]38]. Four studies with hemophiliacs from university clinics [10,15,17,32]; two studies that used national records of hemophiliacs [11,22]; two studies did not report such information [13,16,19,21,39].…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies involved individuals with hemophilia from hospitals or centers specialized in hematological treatment [4,6,7,9,12,14,[18][19][20]30,31,[33][34][35][36]38]. Four studies with hemophiliacs from university clinics [10,15,17,32]; two studies that used national records of hemophiliacs [11,22]; two studies did not report such information [13,16,19,21,39].…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Sixteen studies endorsed the condition of oral hygiene/dental plaque [4,6,7,10,[13][14][15][16][19][20][21][22]31,32,34,39]. Twelve studies have evaluated the gingival condition [4,6,7,15,[17][18][19][20]32,35,38,39]. Other aspects such as temporomandibular dysfunction [12,31], malocclusion [18,31], active dental caries in enamel [15], and hypoplasia [31] were evaluated alone.…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, incorporating dental care as a part of the specialized hemophilia centers may enhance confidence and acceptance of the dental care and help to decrease the risk of bleeding during dental appointments [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an increase in the dmft/DMFT scores of young hemophilia patients [65][66][67]. However, other reports found comparable caries indices in hemophilia patients as in healthy individuals [68,69]. In fact, even a lower prevalence of caries has been shown in young hemophilia patients compared to the general population of Northern Ireland [70].…”
Section: Coagulation Defects and Oral Healthmentioning
confidence: 99%